A Selective Ion HPLC-APCI-MS Method for the Quantification of Pentacyclic Triterpenes in an Anxiolytic Botanical Dietary Supplement for the Animal Health Market - Liu, Rui (2019)
A new anti-anxiety dietary supplement was developed for the animal health market, by combining 2 triterpene containing botanicals, Souroubea sympetala (Marcgraviaceae) with Platanus occidentalis (Platanaceae) A validated method for a quality control of the botanical blend was achieved using HPLC-APCIMS. The method resulted in the detection and quantitative determination of betulinic acid (1), and ursolic acid (2) in P. occidentalis and 1, 2, lupeol (3), β-amyrin (4) and α-amyrin (5) in S. sympetala and the finished product ZentrolTM. Detections were at low ng on column for 1 and 2 and in low µg range for 3, 4 and 5 using calibration curves within 10-100 ng (R2 > 0.993). Recovery of spiked samples for all the recoveries observed were > 94%. Inter-day and intraday variations were 0.8-3.5% and 5-10.4%, respectively. These results indicate the suitability of the developed analytical method to detect and quantify triterpenes of raw materials used in the manufacture of natural health products